Answer:
Ax =
⇒ 3rd answer
Explanation:
Lets revise the Cramer's rule
- If the system of equation is ax + by = c and dx + ey = f
- A is the matrix represent this system of equation
- The first column has the coefficients of x, and
the second column has the coefficients of y
∴ A =
![\left[\begin{array}{cc}a&b\\d&e\end{array}\right]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lgxyqrhjrb1tc0yifq26dyoornr016x0qf.png)
- Ax means replace the column of x by the answers of the equation
∴ Ax =
![\left[\begin{array}{cc}c&b\\f&e\end{array}\right]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2knsy6b9aplgtce57pn1bp5xekte1ss5g8.png)
- Ay means replace the column of y by the answers of the equation
∴ Ay =
![\left[\begin{array}{cc}a&c\\d&f\end{array}\right]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vy8agdblgl8kzrmejweml0eorzjb0h7435.png)
* Now lets solve the problem
∵ 4x - y = -3 and -2x + y = 5
∴ A =
![\left[\begin{array}{cc}4&-1\\-2&1\end{array}\right]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1x9l6fz0bzl189j9dkzp91ow5k5mck76zs.png)
- Replace the column of x by the answer to get Ax
∴ Ax =
![\left[\begin{array}{cc}-3&-1\\5&1\end{array}\right]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8wnf16ywoeyc1jdwpj7jdrj2sbs4gsfl1b.png)
* Ax in the system of equation is
![\left[\begin{array}{cc}-3&-1\\5&1\end{array}\right]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8wnf16ywoeyc1jdwpj7jdrj2sbs4gsfl1b.png)